Spontaneously hypertensive rat as experimental model of salivary hypofunction - Picco, Daniele C. R. [UNESP]; Costa, Lilian F. [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Sassaki, Kikue T. [UNESP]; Sumida, Doris Hissako [UNESP]; Silva, Cristina Antoniali [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Objective: To analyse the salivary activity in spontaneously hypertensive rats (SHRs) evaluating biochemical parameters of saliva in 4-week-old and 12-week-old animals.Design: Systolic blood pressure (SBP) was recorded by tail plethysmography. The salivary flow rate was stimulated by pilocarpine (SFR). The pH and salivary buffering capacity (SBC) were evaluated with a specific electrode. The concentrations of fluoride ([F-]) and calcium ([Ca++]) ions were determined using an electrode connected to a calibrated ion analyser. The total protein concentration was determined by Lowry method, and amylase activity by kinetic method. The salivary IgA was determined by enzyme-linked immunosorbent assay (ELISA).Results: The SFR, [F-] and [Ca++] increased with age in normotensive rats, however no alteration in pH, total protein and IgA was observed between 4 and 12 weeks old Wistar rats. SBC decreased with age in Wistar rats. The SFR was not altered between SHRs in different ages and it was lower in 12 weeks old SHR when compared to Wistar rats. An increase in the protein concentration, and in the amylase activity and [F-] was observed with the development of SHR. Unaltered SBC, salivary IgA and [Ca++] were observed in 12 weeks old when compared to 4 weeks old SHR. The [Ca++] ions were reduced in saliva of SHR than that of Wistar rats at 12 weeks. A lower pH was observed in saliva of Wistar than that of SHR at 12 weeks.Conclusions: SHR is an experimental model of salivary hypofunction, the decreased SFR observed in SHR at different ages was associated to salivary biochemical parameter alterations. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Hypertension; Salivary glands; Saliva; SHR